Centrality of Early Synaptopathy in Parkinson’s Disease - Imbriani, Paola; Schirinzi, Tommaso; Meringolo, Maria; Mercuri, Nicola B.; Pisani, Antonio (Frontiers in Neurology, 2018)
Significant advances have been made in the understanding of the numerous mechanisms involved in Parkinson’s disease (PD) pathogenesis. The identification of PD pathogenic mutations and the use of different animal models have contributed to better elucidate the processes underlying the disease. Here, we report a brief survey of some relevant cellular mechanisms, including autophagic-lysosomal dysfunction, endoplasmic reticulum (ER) stress and mitochondrial impairment, with the main aim to focus on their potential convergent roles in determining early alterations at synaptic level, mainly consisting in a decrease in dopamine release at nigrostriatal terminals and loss of synaptic plasticity at corticostriatal synapses. In a number of experimental models, this synaptopathy has been shown to be an initial, central event in PD pathogenesis, preceding neuronal damage, thereby representing a valuable tool for testing potential disease-modifying treatments.